Peningkatan Potensi Ekonomi Digital Perempuan Desa Batusari Bersama Kampus Shopee Semarang - Trisnapradika, Gustina Alfa; Nissa, Khoirul; Prayogo, Sandi Yudha; Rizky, Muhammad Ivan Khoirur (Community : Jurnal Pengabdian Pada Masyarakat, 2024)
For some, the role of housewives is often underestimated because it is called an unproductive role. In fact, housewives have many skills and capabilities in self-development if they find the right place. Desa Batursari has a population demographic with a high population of 35,229 people. Of the total population, 17,625 are women. This is also a high potential for carrying out various aspects of empowerment and increasing competence for women, especially housewives. Housewives in Desa Batursari have many skills in producing creative goods and processed food products but are constrained in marketing which is only by word of mouth. Therefore, the Community Service Team collaborated with the Kampus UMKM Shopee Semarang to provide appropriate digital marketing education and training for housewives in Desa Batursari. The activity was held with a presentation of the education followed by the practice of optimizing digital marketing in the marketplace. It is hoped that with this community service activity, housewives in Desa Batursari can increase the economic potential of themselves and their families.